Analysis of Availability of Facilities and Service Quality on Satisfaction Study of Kaili and Tanah Women's Literature - Indah Ahdiah; Nanang Wijaya; Alimudin; Andi Famrizal; Ermi; Mufrihullah V.A. Diniy (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Knowing the existence of women through in-depth studies and taking from various references, then publishing it is believed that it can produce a broader understanding for equal human development. This article is written with the aim of revealing the existence of Kaili Women in the existing scientific literature until 2024. By knowing scientific writings that focus on discussing the relationship between Kaili women and the soil, it can provide data in an effort to improve the use of more humane humans. The data collection method used literature studies, reference searches were carried out on google scholar, with the keyword 'women kaili, land'. The two words are the focus that will be developed in further research that will be analyzed in more detail. The results of the study found five writings about Kaili women, and three writings that reveal the relationship between Kaili women and the land as a natural environment that forms a social environment. This column about Kaili women will be the primary data in a more in-depth search of the position of Kaili women in a broader study.